2011
DOI: 10.1371/journal.pgen.1002075
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis between Beneficial Mutations and the Phenotype-to-Fitness Map for a ssDNA Virus

Abstract: Epistatic interactions between genes and individual mutations are major determinants of the evolutionary properties of genetic systems and have therefore been well documented, but few quantitative data exist on epistatic interactions between beneficial mutations, presumably because such mutations are so much rarer than deleterious ones. We explored epistasis for beneficial mutations by constructing genotypes with pairs of mutations that had been previously identified as beneficial to the ssDNA bacteriophage ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
136
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(146 citation statements)
references
References 51 publications
(56 reference statements)
9
136
1
Order By: Relevance
“…In addition, we found that the effect of epistasis between the topA and pykF mutations was negatively correlated with the growth rate of the strain containing the mutations, which is consistent with previous studies [8,9,23]. This result suggests that our focal mutations may affect a common saturating physiological process, which is related to growth rate.…”
Section: (B) Epistasis Depends On Genetic Backgroundsupporting
confidence: 92%
“…In addition, we found that the effect of epistasis between the topA and pykF mutations was negatively correlated with the growth rate of the strain containing the mutations, which is consistent with previous studies [8,9,23]. This result suggests that our focal mutations may affect a common saturating physiological process, which is related to growth rate.…”
Section: (B) Epistasis Depends On Genetic Backgroundsupporting
confidence: 92%
“…Recent studies have found that epistatic interactions between beneficial mutations and their genetic backgrounds tend to become increasingly negative as the fitness of the genetic background increases (11)(12)(13)(14)(15)(16). If this relationship also holds across diverse recipient strains, we predict a negative relationship between the absolute fitness of a strain (measured as growth rate) and the benefit conferred by addition of a mutation.…”
Section: Fitter Recipient Strains Benefit Less From Introduced Mutatimentioning
confidence: 75%
“…Epistasis plays a key role in many aspects of biology, including theories of speciation (2,3), the evolution and maintenance of sex (4,5), adaptation (6)(7)(8), and evolutionary contingency (9,10). Whereas early experimental studies focused on interactions between deletion or other knockout mutations, advances in genomic technologies now allow direct tests of interactions between spontaneously occurring beneficial mutations (11)(12)(13)(14)(15)(16). Studies that manipulate beneficial mutations have the potential to identify general patterns that may underlie some degree of predictability in adaptive evolutionary outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations